Subclasses of Starlike Functions Associated with Fractional q-Calculus Operators. (28th April 2013) - Murugusundaramoorthy, G.; Selvaraj, C.; Babu, O. S.
Abstract : Making use of fractional q -calculus operators, we introduce a new subclass ℳ q ( λ, γ, k ) of starlike functions and determine the coefficient estimate, extreme points, closure theorem, and distortion bounds for functions in ℳ q ( λ, γ, k ) . Furthermore we discuss neighborhood results, subordination theorem, partial sums, and integral means inequalities for functions in ℳ q ( λ, γ, k ) .